2012
DOI: 10.1007/s00438-012-0696-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of WRKY transcription factors in Solanum lycopersicum

Abstract: The WRKY transcription factors have been implicated in multiple biological processes in plants, especially in regulating defense against biotic and abiotic stresses. However, little information is available about the WRKYs in tomato (Solanum lycopersicum). The recent release of the whole-genome sequence of tomato allowed us to perform a genome-wide investigation for tomato WRKY proteins, and to compare these positively identified proteins with their orthologs in model plants, such as Arabidopsis and rice. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
304
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(340 citation statements)
references
References 61 publications
19
304
0
Order By: Relevance
“…Tandem duplication was two or more genes located on the same chromosome within the range of 100 kb distance, while the segmental duplication means the homologous genes duplicated on different chromosomomes. 65,66) In this study, the results showed the SlHZ genes were distributed at all the 12 chromosomes. SlHZ genes were distributed with high density at chromosome II and III, each contained nine genes.…”
Section: Slhz Gene Family In Tomato Genomementioning
confidence: 51%
“…Tandem duplication was two or more genes located on the same chromosome within the range of 100 kb distance, while the segmental duplication means the homologous genes duplicated on different chromosomomes. 65,66) In this study, the results showed the SlHZ genes were distributed at all the 12 chromosomes. SlHZ genes were distributed with high density at chromosome II and III, each contained nine genes.…”
Section: Slhz Gene Family In Tomato Genomementioning
confidence: 51%
“…The results showed that 69 SiWRKY proteins contained one or two identical WRKYGQK domains. Although the WRKYGQK domain is highly conserved in WRKY proteins, SiWRKY59 and SiWRKY60 differed at one residue, with a glutamine being replaced by a lysine residue; this change is also found in WRKYs from tomato, Arabidopsis, and other plant species [13,15,19,22]. Additionally, most of the SiWRKY proteins contained the C-X 4-7 -C-X 23 -H motif that forms the C 2 H 2 /C 2 HC-type zinc-finger structure.…”
Section: Classification and Phylogenetic Analysis Of The Siwrky Genesmentioning
confidence: 99%
“…The first identified WRKY gene, SPF1, was cloned from sweet potato (Ipomoea batatas) 20 years ago [16]. Since then, a large number of WRKY genes have been identified, including 74 from Arabidopsis thaliana [17], 103 from Oryza sativa [18], 45 from Hordeum vulgare [19], 119 from Zea mays [20], and many more from other plant species [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 22 candidate genes, 5 belonged to the NBS-LRR family, 3 were receptor-like protein kinase family members, 3 were transcription factors, 2 were protein isomerases, 2 were involved in oxidation reduction in organisms, 1 encoded structural proteins, 1 encoded allergic pathogenic proteins, 2 were ubiquitin ligases, and 1 was related to cytochromes. According to the gene clusters and tandem repeats criteria used in previous studies (Meyers et al, 2003;Yang et al, 2008;Huang et al, 2012), further analysis revealed that the 5 NBS-LRR family genes in the Ty-2 disease-resistant genes region belonged to 2 gene clusters. Solyc11g069620.1.1 and Solyc11g069660.1.1 belonged to the same gene cluster, and exhibited tandem repeat modes; the other 3 NBS-LRR family genes (Solyc11g069920.1.1, Solyc11g069990.1.1, and Solyc11g070000.1.1) belonged to another cluster.…”
Section: Identification Of Ty-2 Candidate Genes In Tomatomentioning
confidence: 99%